Short-term IL-15 priming leaves a long-lasting signalling imprint in mouse NK cells independently of a metabolic switch - Luu, Thuy T (Life Sci Alliance, 2021)
IL-15 priming of NK cells is a broadly accepted concept, but the dynamics and underlying molecular mechanisms remain poorly understood. We show that as little as 5 min of IL-15 treatment in vitro, followed by removal of excess cytokines, results in a long-lasting, but reversible, augmentation of NK cell responsiveness upon activating receptor cross-linking. In contrast to long-term stimulation, improved NK cell function after short-term IL-15 priming was not associated with enhanced metabolism but was based on the increased steady-state phosphorylation level of signalling molecules downstream of activating receptors. Inhibition of JAK3 eliminated this priming effect, suggesting a cross talk between the IL-15 receptor and ITAM-dependent activating receptors. Increased signalling molecule phosphorylation levels, calcium flux, and IFN-γ secretion lasted for up to 3 h after IL-15 stimulation before returning to baseline. We conclude that IL-15 rapidly and reversibly primes NK cell function by modulating activating receptor signalling. Our findings suggest a mechanism by which NK cell reactivity can potentially be maintained in vivo based on only brief encounters with IL-15 trans-presenting cells.